Biomedical engineering systems and technologies : 5th International Joint Conference, BIOSTEC 2015, Lisbon, Portugal, January 12-15, 2015, Revised selected papers /: 5th International Joint Conference, BIOSTEC 2015, Lisbon, Portugal, January 12-15, 2015, Revised selected papers. (2015) - Unknown
No abstract available